Applying a Deep Learning Pedagogical Model in Physical Education and Health Learning - Amalia Rizki Rahmadani; Rumini (Gladi : Jurnal Ilmu Keolahragaan, 2026)
This study examines the implementation of the Deep Learning model in Physical Education, Sports, and Health (PJOK) learning at YSKI Christian High School, Semarang. Deep learning emphasizes meaningful, reflective, and contextual learning experiences that foster students’ higher-order thinking and real-life application of physical activity. A descriptive qualitative approach was employed involving PJOK teachers and Grade XI students. Data were collected through interviews, observations, documentation, and student questionnaires and analyzed using triangulation of sources, methods, and time. The findings indicate that the Deep Learning model is implemented through three core principles: Meaningful Learning, Mindful Learning, and Joyful Learning. These principles enhance students’ cognitive engagement, understanding of learning purposes, and ability to apply physical activities in daily life. Institutional support, technological readiness of teachers and students, and a supportive learning environment emerged as key facilitating factors. However, limited instructional time and variations in students’ digital literacy remain challenges. The use of digital platforms such as Kahoot, Quizizz, and SiSKY significantly increases learning interactivity and motivation. Overall, the Deep Learning model contributes positively to improving PJOK instructional quality and students’ critical, collaborative, and reflective skills.